An overview of the role of sympathetic regulation of immune responses in infectious disease and autoimmunity. (17th February 2018) - Bucsek, Mark J.; Giridharan, Thejaswini; MacDonald, Cameron R.; Hylander, Bonnie L.; Repasky, Elizabeth A.
Abstract: Stress in patients and pre-clinical research animals plays a critical role in disease progression Activation of the sympathetic nervous system (SNS) by stress results in secretion of the catecholamines epinephrine (Epi) and norepinephrine (NE) from the adrenal gland and sympathetic nerve endings. Adrenergic receptors for catecholamines are present on immune cells and their activity is affected by stress and the accompanying changes in levels of these neurotransmitters. In this short review, we discuss how this adrenergic stress impacts two categories of immune responses, infections and autoimmune diseases. Catecholamines signal primarily through the β2-adrenergic receptors present on innate and adaptive immune cells which are critical in responding to infections caused by pathogens. In general, this adrenergic input, particularly chronic stimulation, suppresses lymphocytes and allows infections to progress. On the other hand, insufficient adrenergic control of immune responses allows progression of several autoimmune diseases.